Preference of Early Childhood Teachers in Using Instructional Media: A Systematic Survey - Zahid Zufar At Thaariq; Khoirunnisa' (SEAMEO CECCEP, 2023)
Instructional media is a fundamental need for teachers, especially those who teach early childhood, in transmitting messages as taught material. Early childhood teachers have certain preferences when developing (by design) or utilizing instructional media, especially in the realm of digitalization. These preferences are tailored to the learning needs of early childhood. This study aims to find the preferences of early childhood teachers in utilizing or developing instructional media. This quantitative research uses a systematic survey (percentage) approach involving 30 early childhood teachers as respondents. The results showed that there was a dominant preference of early childhood teachers in optimizing instructional media. These preferences include LCD Projectors, traditional whiteboards, wall magazines, Microsoft Word, self-drawing, smartphone cameras, voice recordings, WhatsApp Call, public television, YouTube live broadcasts, Zoom, Capcut, Google, WhatsApp, Google Form and Google Classroom. This means that early childhood teachers' understanding of instructional media is good, but needs to be strengthened in their digitization capabilities. Thus, this research can be used as an alternative reference in empowering early childhood teachers in the future.